Intrapartum uterine activity and neonatal outcomes: a systematic review - Adam J. Reynolds; Michael P. Geary; Breda C. Hayes (BMC, 2020)
Abstract Background Increased uterine activity (UA) may not allow adequate recovery time for foetal oxygenation. Methods The aim of the study was to determine if increased UA during labour is associated with an increased risk of either short- or long-term neurological injury in term neonates, or with neonatal proxy measures of intrapartum hypoxia-ischemia. MEDLINE, CINAHL, and ClinicalTrials.gov were searched using the following terms: uterine activity, excessive uterine activity, XSUA, uterine hyperstimulation, and tachysystole. Any study that analysed the relationship between UA during term labour and neurological outcomes/selected proxy neurological outcomes was eligible for inclusion. Outcomes from individual studies were reported in tables and presented descriptively with odds ratios (OR) and 95% confidence intervals (CI) for dichotomous outcomes and means with standard deviations for continuous outcomes. Where group numbers were provided, ORs and their CIs were calculated according to Altman. Main results Twelve studies met the inclusion criteria. Seven studies featured umbilical artery pH as an individual outcome. Umbilical artery base excess and Apgar scores were both reported as individual outcomes in four studies. No study examined long term neurodevelopmental outcomes and only one study reported on encephalopathy as an outcome. The evidence for a relationship between UA and adverse infant outcomes was inconsistent. The reported estimated effect size varied from non-existent to clinically significant. Conclusions There is some evidence that increased UA may be a non-specific predictor of depressed neurological function in the newborn, but it is inconsistent and insufficient to support the conclusion that an association generally exists.